A comprehensive overview of the cystic fibrosis on the island of São Miguel (Azores, Portugal) - Rosa, Joana (2021)
Background: Early diagnosis and treatment are improving significantly the quality of life of patients with cystic fibrosis (CF). This recessive disease is caused by a great variability of mutations in the CF transmembrane conductance (CFTR) gene, whose spectrum and frequency can be different across populations. Methods: We performed a retrospective cross-sectional study of CF patients from the island of São Miguel (Azores, Portugal) through a clinical, genealogical, genetic and epidemiological investigation. The clinical course of patients was analyzed as a whole and according to their genotype. Results: We identified 14 CF patients within a 23-year period, corresponding to a cumulative incidence of 1:3012 births, being three of them born from consanguineous unions. Genetic analysis revealed three CFTR genotypes: p.[Ser4Ter];[Gln1100Pro] was present in one patient with a less severe phenotype (1/14); c.[120del23];p.[Phe508del], a very rare one (2/14); and p.[Phe508del];[Phe508del] in the remaining patients (11/14). Clinically, respiratory infections (8/14) and growth failure (6/14) were the most common initial manifestations. All patients presented pancreatic dysfunction, with 21.4 and 100% of them showing endocrine and exocrine insufficiency, respectively. As expected, patients with severe phenotype were homozygous for p.Phe508del and had the lowest value of body mass index. Conclusions: The present study demonstrated that São Miguel Island has an increased incidence of CF when compared to recent Portuguese data (1:7500 live births). It also allowed a comprehensive overview of CF in São Miguel, improving medical practice along with genetic counselling and creating opportunities for genotype-targeted therapies.